Migrant returnees as (anti-)migration messengers? A case of street-level representative bureaucracy in Senegal - Katerina Glyniadaki; Nora Ratzmann; Julia Stier (International Migration, 2025)
International organizations and foreign-funded NGOs run campaigns in Senegal to raise awareness of the perils of irregular migration. To increase their effectiveness, these organizations often enlist local migrant returnees to share their personal migration experiences and transmit an anti-irregular migration message to their compatriots. This article examines whether policymakers' assumptions regarding the representativeness of migrant returnees operating as (anti-)migration messengers in terms of shared identities corresponds to reality at the street level. It draws from theories of street-level bureaucracy and representative bureaucracy and is based on 31 qualitative interviews with migrant returnees and experts. The study shows that migrant returnees engaged in migration information campaigns are not as representative of the local population as envisaged by policymakers, potentially impacting policy outcomes. They stand out from their compatriots in terms of skillsets and social status – partly because of the selection mechanism employed by organizations and partly because of the training and capacity-building efforts directed at migrant returnees.
Keywords: 330